2017
DOI: 10.4314/bajopas.v9i2.23
|View full text |Cite
|
Sign up to set email alerts
|

Levels of total phenolic and flavonoids in <i>Abelmoschus esculentus</i> L. from some irrigation areas of Kano state-Nigeria

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Similar to our findings, previous research presented a similar level of TPC varied from 33.33 ± 0.02 to 37.38 ± 4.22 mg GAE g −1 ( Mohammed et al , 2016 ). While, previous studies have reported a similar phenolic level in okra fruits (49.72 ± 2.24 mg GAE g −1 ) ( Rohman et al , 2010 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to our findings, previous research presented a similar level of TPC varied from 33.33 ± 0.02 to 37.38 ± 4.22 mg GAE g −1 ( Mohammed et al , 2016 ). While, previous studies have reported a similar phenolic level in okra fruits (49.72 ± 2.24 mg GAE g −1 ) ( Rohman et al , 2010 ).…”
Section: Discussionsupporting
confidence: 92%
“…Literature has explained these results by the dilution effect slowing the biosynthesis of new phenolic compounds which increase the size during ripening for fruits (Anand and Aradhya, 2005). Accordingly, with our results, Mohammed et al (2016) indicated okra fruit flavonoid contents about 29.979 ± 0.036 mg RE g −1 . In addition, similar flavonoid contents of okra fruits have been earlier expressed (31.21 ± 8.64 mg RE g −1 ) ( Rohman et al , 2010 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The four quercetin derivatives and epigallocatechin were first time reported in okra [14]. A. esculentus fruit is rich in phenolics and flavonoids may be serve as good source of natural antioxidants [15,16]. Along with cultivated some wild species also rich in antioxidants [20].…”
Section: Phytochemical Analysis Of Genus Abelmoschusmentioning
confidence: 99%
“…Buah okra yang sudah tua, rasanya liat dan tidak layak untuk dikonsumsi. Khomsug et al (2010); Hu et al (2013); Mohammed et al (2016) melaporkan buah okra mengandung senyawa fenolik dan flavonoid. Hamid et al (2010) berpendapat senyawa fenolik dan flavonoid merupakan antioksidan alami yang lebih aman daripada antioksidan sintetik karena mampu meredam radikal bebas dalam tubuh manusia, sehingga mencegah penyakit degeneratif.…”
Section: Pendahuluanunclassified